2007
DOI: 10.12968/hmed.2007.68.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis: principles of management

Abstract: Diabetic ketoacidosis has a mortality of up to 14% in the UK, which could be attributed to varied treatment policies and a lack of a general consensus statement on its management. This article provides comprehensive guidelines for management of adult patients in diabetic ketoacidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Free fatty acids lead to into ketonemia and ketonuria by beta oxidation. 12 In our study mean age of the patients with DM-II was 50.09 ± 9.39 years, comparable mean age of the patients with DM-II was reported by Sheikh et al 8 Mean age of the patients with DM-II reported by Pinto et al 13 in their study was 45±12 which is also in agreement with our study. In present study male patients was 42% and female patients were 58% which is comparable with a study by Sheikh et al, 8 in his study male patients were 38.6% and female patients were 61.4%.…”
Section: Discussionsupporting
confidence: 92%
“…Free fatty acids lead to into ketonemia and ketonuria by beta oxidation. 12 In our study mean age of the patients with DM-II was 50.09 ± 9.39 years, comparable mean age of the patients with DM-II was reported by Sheikh et al 8 Mean age of the patients with DM-II reported by Pinto et al 13 in their study was 45±12 which is also in agreement with our study. In present study male patients was 42% and female patients were 58% which is comparable with a study by Sheikh et al, 8 in his study male patients were 38.6% and female patients were 61.4%.…”
Section: Discussionsupporting
confidence: 92%
“…Mortality was 14% in UK, 4% in Denmark, 11.8% in Korea and 29.8% in Kenya. 21,22,10,12 . With better understanding of the pathophysiology of DKA and improvements in treatment, outcome is improving 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…All other patients recovered. In the UK 17 , in-hospital mortality rate was upto 14% because of variations in management and various other factors, in Denmark 16 it was 4% and in Korea 14 , in-hospital mortality was 11.8%. In Nairobi 13 29.8% patients expired in hospital within 48 hours of admission.…”
Section: Discussionmentioning
confidence: 99%